2020
DOI: 10.1080/08998280.2019.1708667
|View full text |Cite
|
Sign up to set email alerts
|

Patient and provider characteristics and outcomes associated with outpatient antibiotic overuse in acute adult bronchitis

Abstract: Nonbacterial acute bronchitis leads to many outpatient clinic visits in the US that result in an antibiotic prescription. Understanding antibiotic prescribing patterns and their clinical consequences will help improve antimicrobial stewardship efforts. A retrospective chart review was conducted to identify any correlations between patient and provider characteristics with antibiotic use in adult acute bronchitis (AAB) and to compare the clinical outcomes and rates of health care utilization between those who d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
2
1
0
Order By: Relevance
“…Previous studies have assessed what provider characteristics predict unnecessary or inappropriate prescribing. Similar to several prior studies [ 35 , 36 ], we found that providers who had spent more years in practice were more likely to give unnecessary prescriptions. In addition, providers in rural settings compared with urban settings were more likely to provide unnecessary antibiotic prescriptions, as seen in studies conducted in different geographic regions [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have assessed what provider characteristics predict unnecessary or inappropriate prescribing. Similar to several prior studies [ 35 , 36 ], we found that providers who had spent more years in practice were more likely to give unnecessary prescriptions. In addition, providers in rural settings compared with urban settings were more likely to provide unnecessary antibiotic prescriptions, as seen in studies conducted in different geographic regions [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 89%
“…Prior studies have identified provider demographics to be associated with higher proportion of antibiotic prescribing or with surrogate metrics of inappropriateness, including female gender (compared to male), APP (compared to physician), family medicine specialty (compared to pediatrician and internal medicine), older age (compared to younger), nonurban practice setting (compared to urban), and southern United States geographic region (compared to western). [21][22][23][24][25][26][27][28][29][30][31][32][33] All of the characteristics that could be assessed in this study had similar associations to prior studies except for time in practice. In this study, less time in practice was associated with a higher proportion of inappropriate antibiotic prescribing, whereas in other studies older providers were associated with higher proportion of inappropriate antibiotic prescribing.…”
Section: Discussionsupporting
confidence: 54%
“…Prior studies have shown that both of these factors are associated with differences in antibiotic prescribing practices. 36 Finally, the study period reflects clinical viral testing and antibiotic prescribing and administration practices prior to the coronavirus disease 2019 (COVID-19) pandemic. Studies have recently reported that during the COVID-19 pandemic, changes in healthcare-seeking behaviors (ie, decreases in visits) led to a dramatic reduction of antibiotic prescriptions (31.6 to 6.4 prescriptions per 1,000 visits) in children for respiratory tract infections 37 ; however, from April to June 2021, studies have shown a rebound in both respiratory tract infections and antibiotic prescriptions.…”
Section: Discussionmentioning
confidence: 99%